Reporting systems for bank management : building a bank management information system - Walker, John R. (Boston : Bankers Pub. Co., 1987)
This book describes how to develop an operational information base for the successful management of a financial institution in today's environment
Includes index.
osc 22/9/2017
Loans
Keywords: Bank management--Data processing